Eurasianism and Foreign Policy of Russia - S. V. Bazavluk (Евразийская интеграция: экономика, право, политика, 2021)
In order to determine the possibilities of wider application of the ideas of Eurasianism in the foreign policy of Russia, including the EAEU, but not limited to it, an analysis of various methods and approaches used for integration processes is carried out. At the same time, the current geopolitical situation and the factors of multi-vector approach in international relations are taken into account. It is also proposed to take in attention the role of identity in a broad sense as a political attraction. At the same time, various problems at the organizational, social, humanitarian and economic levels are also considered. The broad security factors that also play a role in the Eurasian integration are also taken into account. The relevance of this study is due not only to the implementation of strategic directions within the EAEU, but also to the general course towards multipolarity that Russia is pursuing. In addition, the crisis of liberal democracy in the West provides an additional opportunity for Russia to implement its own ideas and doctrines at the international level. The author believes that Eurasianism, including its classical version, can become one of the imperatives of Russia’s foreign policy.